EKSTRAKSI MINYAK DAN RESIN NYAMPLUNG DENGAN CAMPURAN PELARUT HEKSAN-ETANOL - Ika Amalia Kartika, Desita Dwi Kurnia Sari,Auradelia Febrian Pahan, Ono Suparno,Danu Ariono (Jurnal Teknologi Industri Pertanian, 2017)
Calophyllum seeds are potential to be used as raw material for vegetable oil production due to their high oil content (75.1% db). In addition, Calophyllum seeds contain resin consistingbeneficial phenolic compounds for health. In this study, Calophyllum seeds were extracted using hexane-ethanol mixture to investigate oil and resin yields and their physicochemical properties, and to obtain the best process condition in oil and resin production from Calophyllum seeds. Experiment was carried out using randomized complete design with threefactors, i.e. extraction times (5-7 h), temperatures (40-50°C), and hexane to ethanol ratios (2:4, 3:3 and 4:2). The result of variance analysis showed that extraction time and hexane to ethanol ratio affected significantly on oil and resin yields, density, acid and iod values, whereas temperature influenced only on oil yield, density and acid value. Best oil (58.2%) and resin (16.2%) yields were respectively obtained at 5h extraction time, 50°C temperature and 4:2 hexane to ethanol ratio, and 5hextraction time, 40°C temperature and 2:4 hexane to ethanol ratio. At these optimum conditions, the oil had acid value of 14.89 mg KOH/g, iodine value of 60.75 g iodine/100 g, viscosity (25°C) of 71.46 mPa.s, and density (25°C) of 0.86 g/cm3. On the other hand, the resin had acid value of 133.76 mg KOH/g. Keywords: Calophyllum, extraction, ethanol, hexane, oil, resin